Genomic epidemiology of human adenovirus F40 and F41 in coastal Kenya: A retrospective hospital-based surveillance study (2013–2022). Issue 1 (24th March 2023) - Lambisia, Arnold W; Makori, Timothy O; Mutunga, Martin; Cheruiyot, Robinson; Murunga, Nickson; Quick, Joshua; Githinji, George; Nokes, D James; Houldcroft, Charlotte J; Agoti, Charles N
Abstract: Human enteric adenovirus species F (HAdV-F) is a leading cause of childhood diarrhoeal deaths. The genomic analysis would be key to understanding transmission dynamics, potential drivers of disease severity, and vaccine development. However, currently, there are limited HAdV-F genomic data globally. Here, we sequenced and analysed HAdV-F from stool samples collected in coastal Kenya between 2013 and 2022. The samples were collected at Kilifi County Hospital in coastal Kenya from children <13 years of age who reported a history of three or more loose stools in the previous 24 hours. The genomes were analysed together with the data from the rest of the world by phylogenetic analysis and mutational profiling. Types and lineages were assigned based on phylogenetic clustering consistent with the previously described criteria and nomenclature. Participant clinical and demographic data were linked to genotypic data. Of ninety-one cases identified using real-time Polymerase Chain Reaction, eighty-eight near-complete genomes were assembled, and these were classified into HAdV-F40 ( n = 41) and HAdV-F41 ( n = 47). These types co-circulated throughout the study period. Three and four distinct lineages were observed for HAdV-F40 (Lineages 1–3) and HAdV-F41 (Lineages 1, 2A, 3A, 3C, and 3D). Types F40 and F41 coinfections were observed in five samples and F41 and B7 in one sample. Two children with F40 and 41 coinfections were also infected with rotavirus and had moderate and severe diseases as defined using the Vesikari Scoring System, respectively. Intratypic recombination was found in four HAdV-F40 sequences occurring between Lineages 1 and 3. None of the HAdV-F41 cases had jaundice. This study provides evidence of extensive genetic diversity, coinfections, and recombination within HAdV-F40 in a rural coastal Kenya that will inform public health policy, vaccine development that includes the locally circulating lineages, and molecular diagnostic assay development. We recommend future comprehensive studies elucidating on HAdV-F genetic diversity and immunity for rational vaccine development.